Genetic confirmation of morphological identified endangered ornamental loach Botia lohachata by mitochondrial CO-I gene, found from Kirthar mountain range Sindh, Pakistan (Zoo Botanica, 2025)
The Botia lohachata were collected from the Ranikot Stream for morphological and molecular characterization. B. lohachata belong to family Botiidae, commonly known as freshwater Loaches and generally as ‘tiger loach’. Currently, it is enlisted in is in IUCN Red List It is a tropical bottom dwelling loach of small to medium-sized riverine loach. The cytochrome coxidase I (CO-I) gene was used to evaluate the species. CO-I gene sequence resulted 707bp. For all the samples, the percentage of Thymine was significantly higher compared to the other nucleotides i.e., 31.54% followed by Adenine and Cytosine i.e 25.74%. While the GC contents were recorded 42.7%. In further, the molarity (1µg/µl) was recorded 2.29µM. The present findings will be helpful in the identification of the Endangered and Vulnerable Botia species. Further, it will be beneficial for future genetic population studies and developing a conservation-scheme approach for managing the fish diversity in their natural habitats.
Keywords: Cytochrome coxidase I (CO-I) gene; conservation; mitochondrial DNA; Botia lohachata